2016
DOI: 10.1080/02786826.2016.1265912
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Sn binary metal particle generation by spray pyrolysis

Abstract: Cu-Sn binary particles were generated via spray pyrolysis from metal salt precursors with ethylene glycol as the co-solvent and reducing agent. The morphology, crystallinity, and elemental distribution of particles were tunable by changing the reaction temperature, residence time, and quench gas flow rate. Hollow porous particles were fabricated with a higher Sn concentration on the particle surface when the furnace set point was 500 C, while solid particles with a lower surface Sn concentration were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…High processing temperature favors the formation of denser product particles, which has also been observed in other aerosol processes. 28,36 As shown in Figures 1, S3, and S4, the core−shell-structured particle has an average diameter of 680 nm and the average ratio of particle to core is 2.2, implying that this core−shell particle can tolerate 1064% volume expansion of the core during the charge/discharge process. The formation of a carbon shell is also supported by the Raman spectrum (Figure S5), with characteristic peaks representing the D and G band of carbon.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…High processing temperature favors the formation of denser product particles, which has also been observed in other aerosol processes. 28,36 As shown in Figures 1, S3, and S4, the core−shell-structured particle has an average diameter of 680 nm and the average ratio of particle to core is 2.2, implying that this core−shell particle can tolerate 1064% volume expansion of the core during the charge/discharge process. The formation of a carbon shell is also supported by the Raman spectrum (Figure S5), with characteristic peaks representing the D and G band of carbon.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The set points of the furnaces were 1273 K. At the end of this continuous process, the product particles were cooled by N 2 gas and collected on a poly­(tetrafluoroethylene) (PTFE) filter. On the basis of the temperature profile of the same equipment at these conditions, the residence time of this process is 1.2 s …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that lithium was accumulated on the wall of the instrument after analyzing the clean-in-place powders. As the thermophoresis was correlated to the temperature difference between the gas flow and the tube wall, we set the temperature of the tube furnace to 973 K to reduce the lithium loss. The last effort was introducing a rapid quench gas after the flame.…”
Section: Resultsmentioning
confidence: 99%
“…However, the particle size is generally large and is hard to reduce limited by the aerosol droplets. By this route, FeNi and CuSn BMNAs with tunable sizes and compositions have been prepared …”
Section: Base Metal Nas For Chemical Catalysismentioning
confidence: 99%